Respiratory Syncytial Virus (RSV) Illness and Prevention in Older Adults - Nordin, Musa Mohd; Musa, Husna (International Journal of Human and Health Sciences (IJHHS), 2025)
Many non-paediatric doctors are less aware that RSV is also an important cause of acute respiratory infections (ARIs) in adults, especially those above 65 years old and adults suffering from co-morbidities such as diabetes, ischaemic heart disease, asthma or who are immunocompromised. Other factors associated with severe RSV disease in older adults include frailty and residence in a nursing home or other long-term care facility. This article discussed the RSV-associated burden among older adults and potential prevention strategies that should be considered. International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 65-68